Peran Mediasi Psychological Safety pada Pengaruh Inclusive Leadership terhadap Innovative Work Behavior - Ahmad Firdaus; Said Almaududi (Ebisma (Economics, Business, Management, & Accounting Journal), 2026)
Innovation is a crucial element for the survival of startup industries operating in a highly competitive and dynamic environment. This study aims to analyze the influence of Inclusive Leadership on Innovative Work Behavior mediated by Psychological Safety among startup employees in the DKI Jakarta area. This study employs a quantitative approach and a survey design. The sample consisted of startup employees selected using a purposive sampling technique, with the criterion of having a minimum working period of several years. Data were collected through the distribution of questionnaires using a Likert scale and analyzed using Structural Equation Modeling (SEM). The results of the analysis indicate that all hypotheses are accepted. Inclusive Leadership is proven to have a positive and significant influence on Innovative Work Behavior, both directly and indirectly through the mediation of Psychological Safety. These findings confirm that leaders who demonstrate inclusivity are able to create a psychologically safe work environment, thereby encouraging employees to take risks and engage in innovative behavior. This study provides important implications for startup management in building a leadership culture that supports innovation.